2023
DOI: 10.5802/aif.3527
|View full text |Cite
|
Sign up to set email alerts
|

Second cohomology groups of the Hopf * -algebras associated to universal unitary quantum groups

Abstract: We compute the second (and the first) cohomology groups of *algebras associated with the universal quantum unitary groups of not necessarily Kac type, extending our earlier results for the free unitary group U + d . The extended setup forces us to use infinite-dimensional representations to construct the cocycles.Résumé. -Nous calculons les deuxièmes (et premiers) groupes de cohomologi des algèbres involutives associées aux groupes quantiques unitaires universels pas nécessairement du type Kac, étendant ainsi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[11,19] Example 6.3 (Cohomology of Pol(𝑈 + 𝐹 ) with 𝐹 = diag(𝑞 −1 , 1, 𝑞) and with trivial coefficients). In [20], it was shown that for 𝐹 ∈ 𝑀 3 (ℂ) positive, H 2 (Pol(𝑈 + 𝐹 ), 𝜀 ℂ 𝜀 ) ≅ 𝑠𝑙 𝐹 (𝑛) = {𝐴 ∈ 𝑀 𝑛 (ℂ)∶ 𝐴𝐹 = 𝐹𝐴, Tr(𝐴𝐹) = Tr(𝐴𝐹 −1 ) = 0}, provided that the eigenvalues of 𝐹 do not form a geometric progression. This agrees with Theorem 6.1 as the only case in which 𝐹 is a positive matrix and satisfies 𝐹 2 = ±𝐼 is for 𝐹 = 𝐼.…”
Section: Leading Tomentioning
confidence: 99%
See 4 more Smart Citations
“…[11,19] Example 6.3 (Cohomology of Pol(𝑈 + 𝐹 ) with 𝐹 = diag(𝑞 −1 , 1, 𝑞) and with trivial coefficients). In [20], it was shown that for 𝐹 ∈ 𝑀 3 (ℂ) positive, H 2 (Pol(𝑈 + 𝐹 ), 𝜀 ℂ 𝜀 ) ≅ 𝑠𝑙 𝐹 (𝑛) = {𝐴 ∈ 𝑀 𝑛 (ℂ)∶ 𝐴𝐹 = 𝐹𝐴, Tr(𝐴𝐹) = Tr(𝐴𝐹 −1 ) = 0}, provided that the eigenvalues of 𝐹 do not form a geometric progression. This agrees with Theorem 6.1 as the only case in which 𝐹 is a positive matrix and satisfies 𝐹 2 = ±𝐼 is for 𝐹 = 𝐼.…”
Section: Leading Tomentioning
confidence: 99%
“…Example In [20], it was shown that for FM3(C)$F\in M_3(\mathbb {C})$ positive, H2(Polfalse(UF+false),εCε)slF(n)={AMnfalse(double-struckCfalse):AF=FA,Trfalse(AFfalse)=Trfalse(AF1false)=0}$\mathrm{H}^2(\operatorname{Pol} (U_F^+), {_\varepsilon \mathbb {C}_\varepsilon }) \cong sl_F(n) =\lbrace A\in M_n(\mathbb {C}) \colon AF=FA, \operatorname{Tr}(AF) = \operatorname{Tr}(AF^{-1}) = 0\rbrace$, provided that the eigenvalues of F$F$ do not form a geometric progression. This agrees with Theorem 6.1 as the only case in which F$F$ is a positive matrix and satisfies F2=±I$F^2=\pm I$ is for F=I$F=I$.…”
Section: Hochschild Cohomology For Scripthfalse(ffalse)$\mathcal {H}(f)$mentioning
confidence: 99%
See 3 more Smart Citations